Global burden of stroke attributable to high systolic blood pressure in 204 countries and territories, 1990–2019 - Li, Junxiao; Zhong, Qiongqiong; Yuan, Shixiang; Zhu, Feng (Frontiers in Cardiovascular Medicine, 2024)
Background High systolic blood pressure (HSBP) is severely related to stroke, although the global burden of stroke associated with HSBP needs to be understood. Materials and methods Data derived from the Global Burden of Disease, Injuries, and Risk Factors Study were used to analyze deaths, disability-adjusted life years (DALYs), age-standardized rates of mortality (ASMR), age-standardized rates of DALY (ASDR), and estimated annual percentage change (EAPC). Results Globally, 52.57% of deaths and 55.54% of DALYs from stroke were attributable to HSBP in 2019, with higher levels in men; the ASMRs and ASDRs in 1990–2019 experienced a decline of 34.89% and 31.71%, respectively, with the highest ASMR- and ASDR-related EAPCs in women. The middle socio-demographic index (SDI) regions showed the most numbers of deaths and DALYs in 2019 and 1990, with a decline in ASMR and ASDR; East Asia shared over 33% of global deaths and DALYs; Central Asia shared the highest ASMR and ASDR; high-income Asia Pacific experienced the highest decline in the ASMR- and ASDR-related EAPCs. Central and Southeast Asia had the highest percentages for deaths and DALYs, respectively, with more ASMR in high-middle SDI; the SDI and human development index were negatively associated with ASMR/ASDR and ASMR/ASDR-related EAPCs in 2019. Conclusion Global deaths and DALYs of stroke attributable to HSBP but none of their age-standardized rates have been on the rise over the past three decades; its disease burden focused especially on men aged 70 years and older in East, Central, and Southeast Asia, and the middle to high SDI regions.